Portfolio of the Private Pension System (SPP) peruvian 1993-2017: An overall review - Romero Cerna, José Salvador (2019)
Objective: this article contributes to the debate on public policies and the various approaches on the role of The Private Pension System (SPP) and its reform. It highlights the importance of the SPP funds in the Peruvian financial system and analyzes the general composition or relative structure of the investment portfolio of the SPP during the period 1993-2017. It uses two classifications: (1) local investments (fixed income and variable income) and abroad; (2) local investments in the government: the financial sector and the real sector. Method: the research approach is descriptive. The statistics of the SPP published by the Superintendency of Banking, Insurance and AFP (SBS) at the end of the period was used. Results: Two stages were identified during the analyzed period, associated with the level of economic activity (economic cycle and financial crises) and with the reforms and regulatory modifications (eligible investments and investment limits) made by the government's regulatory agencies. Conclusions: the results suggest that the offer of SPP funds to the Peruvian financial system has meant a redistribution of savings to the investment alternatives (savings) of the SPP regulated by the government, and that has been channeled preferentially to the corporate segment, first through the banking sector and then through the stock market, and the Peruvian government.